The ethnological approach in Vietnamese studies: The emergence of vietnamese studies in japan in relation to the development of French ethonography: Case study of Matsumoto Nobushiro's research - Karlova', Petra (H. : ĐHQGHN, 2017)
This paper aims to clarify the significance of the French research of Indochina for the development of the Japanese research of Southeast Asia, especially of Vietnam. Indochina studies which were parts of South Seas studies in the pre-war period were the predecessor of Vietnamese studies. The author of the first systematic research in Indochina, Matsumoto Nobuhiro2, belongs among important Japanese scholars of these studies. Therefore, the study case of his writings can contribute to the understanding of the formation of the ethnological and non- Sinocentric stream in Japan’s Southeast Asian studies that cannot be explained only from the perspective of the Japanese Oriental studies in the first half of the twentieth century.